The Potential of Endophytic Fungi Producing Hydrolytic Enzymes as Biocontrol Agents of Alternaria porri Causing Onion Purple Blotch - Firdausi, Wita; Abadi, Abdul Latief; Aini, Luqman Qurata; Martosudiro, Mintarto; Tarno, Hagus (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Purple blotch caused by Alternaria porri is the primary disease in shallots, causing yield losses of 30-100%. The use of endophytic fungi as biocontrol agents has several advantages, including adaptability to host plants, selective targeting of pathogenic fungal cell walls without harming plant cells, and environmental friendliness. This study aims to select endophytic fungi producing hydrolytic enzymes with the highest inhibitory effect against A. porri. Endophytic fungi were isolated from the Batu Ijo local variety of shallots in Dau District, Malang, then evaluated for antagonism and for their ability to produce hydrolytic enzymes. This study obtained 42 isolates, consisting of 25 fungi and 17 yeasts. The endophytic fungi with the highest inhibitory activity were identified as Trichoderma asperellum (71.4%) and Pichia onychis (70.04%). T. asperellum produced cellulase at concentrations of 16.78 µg/ml and chitinase at 3.85 µg/ml, while P. onychis produced cellulase at concentrations of 11.47 µg/ml and chitinase at 1.56 µg/ml. Microscopic observation of A. porri hyphae showed that both endophytic fungi caused lysis with hyphal fragmentation, discoloration, and deformation. The endophytic fungi T. asperellum and P. onychis were proven to inhibit A. porri in vitro through their ability to produce hydrolytic enzymes that caused A. porri hyphal lysis.